Epidemiology of Perceived Physical Fatigability in Older Adults: The Long Life Family Study - LaSorda, Kelsea R (J Gerontol A Biol Sci Med Sci, 2019)
BACKGROUND: Fatigability is a construct that measures whole-body tiredness anchored to activities of a fixed intensity and duration; little is known about its epidemiology and heritability. METHODS: Two generations of family members enriched for exceptional longevity and their spouses were enrolled (2006–2009) in the Long Life Family Study (LLFS). At Visit 2 (2014–2017, N = 2,355) perceived physical fatigability was measured using the 10-item self-administered Pittsburgh Fatigability Scale (PFS), along with demographic, medical, behavioral, physical, and cognitive risk factors. RESULTS: Residual genetic heritability of fatigability was 0.263 (p = 6.6 × 10(–9)) after adjustment for age, sex, and field center. PFS physical scores (mean ± SD) and higher physical fatigability prevalence (% PFS ≥ 15) were greater with each age strata: 60–69 (n = 1,009, 11.0 ± 7.6, 28%), 70–79 (n = 847, 12.5 ± 8.1, 37%), 80–89 (n = 253, 19.3 ± 9.9, 65.2%), and 90–108 (n = 266, 28.6 ± 9.8, 89.5%), p < .0001, adjusted for sex, field center, and family relatedness. Women had a higher prevalence of perceived physical fatigability compared to men, with the largest difference in the 80–89 age strata, 74.8% versus 53.5%, p < .0001. Those with greater body mass index, worse physical and cognitive function, and lower physical activity had significantly higher perceived physical fatigability. CONCLUSIONS: Perceived physical fatigability is highly prevalent in older adults and strongly associated with age. The family design of LLFS allowed us to estimate the genetic heritability of perceived physical fatigability. Identifying risk factors associated with higher perceived physical fatigability can inform the development of targeted interventions for those most at risk, including older women, older adults with depression, and those who are less physically active.